Improved synthesis of tetraaryl-1,4-dihydropyrrolo[3,2-b]pyrroles a promising dye for organic electronic devices: An experimental and theoretical approach - Martins, Lucas Michelão [UNESP]; de Faria Vieira, Samuel [UNESP]; Baldacim, Gabriel Baldo [UNESP]; Bregadiolli, Bruna Andressa [UNESP]; Caraschi, José Cláudio [UNESP]; Batagin-Neto, Augusto [UNESP]; da Silva-Filho, Luiz Carlos [UNESP] (Elsevier, 2018)
Pyrrolo-[3,2-b]pyrroles represent a class of promising materials for application in organic electronics with interesting optoelectronic properties and great synthesis versatility, but yields obtained from varied synthetic routes are still very low, hindering their effective application for industrial purposes. In this report, we present a method for the synthesis of tetraaryl-1,4-dihydropyrrolo-[3,2-b]pyrrole derivatives by multicomponent reactions employing niobium pentachloride as a catalyst. The optical characterization of the products is also presented. Electronic structure calculations were performed to help the interpretation of the synthesis process, as well as the optical properties of the systems. Excellent yields and low reaction times were obtained, indicating that NbCl5 is an efficient catalyst for such systems. The products show promising properties for optoelectronic applications that can be adjusted by the choice of benzaldehyde derivatives used in the synthesis.
Keywords: Density functional calculations; Fluorescence; Heterocycles; Multicomponent reactions; Niobium pentachloride